Components of the 400m hurdles - Boyd, R.
Author describes the the four stages of the 400m hurdles race: 1. Start to First Hurdle 2. Movement Across Hurdle On Straight On Curve 3. Running Between Hurdles 4. Last Hurdle to Finish With advice for the technical training.